Imbalance in pro-inflammatory and anti-inflammatory cytokines milieu in B cells of children with autism. (January 2022) - Nadeem, Ahmed; Ahmad, Sheikh F.; Al-Harbi, Naif O.; AL-Ayadhi, Laila Y.; Sarawi, Wedad; Attia, Sabry M.; Bakheet, Saleh A.; Alqarni, Saleh A.; Ali, Nemat; AsSobeai, Homood M.
Highlights: B cells of children with autism spectrum disorder (ASD) had elevated expression of inflammatory cytokines. B cells of children with ASD had decreased expression of anti-inflammatory cytokine. TLR4 activation caused enhanced IL-6 levels in B cells of children with ASD. NF k B inhibition reduced LPS-induced IL-6 levels in B cells of ASD subjects. Abstract: B cells play multiple roles in preservation of healthy immune system including management of immune responses by expression of pro- and anti-inflammatory cytokines. Several earlier studies have documented that B cells express both pro-inflammatory cytokines such as IL-6, TNF-α as well as anti-inflammatory cytokines such as IL-10. However, it is yet to be examined whether these pro-/anti-inflammatory cytokines are expressed in B cells of children with autism spectrum disorder (ASD). Pathophysiology of ASD begins in early childhood and is characterized by repetitive/restricted behavioral patterns, and dysfunction in communal/communication skills. ASD pathophysiology also has a strong component of immune dysfunction which has been highlighted in numerous earlier publications. In this study, we specifically explored pro-/anti-inflammatory cytokines (IL-6, IL-17A, IFN-γ, TNF-α, IL-10) in B cells of ASD subjects and compared them typically developing control (TDC) children. Present study shows that inflammatory cytokines such as IL-6 and TNF-α are elevated in B cells of ASD subjects, while anti-inflammatory cytokine, IL-10 is decreased in ASD group when compared to TDC group. Further, TLR4 activation by its ligand, lipopolysaccharide (LPS) further upregulates inflammatory potential of B cells from ASD group by increasing IL-6 expression, whereas LPS has no significant effect on IL-10 expression in ASD group. Furthermore, LPS-induced inflammatory signaling of IL-6 in B cells of ASD subjects was partially mitigated by the pretreatment with NF- k B inhibitor. Present study propounds the idea that B cells could be crucial players in causing immune dysfunction in ASD subjects through an imbalance in expression of pro-/anti-inflammatory cytokines.